2001
DOI: 10.1097/00005373-200101000-00019
|View full text |Cite
|
Sign up to set email alerts
|

2,576 Ultrasounds for Blunt Abdominal Trauma

Abstract: Emergency US is highly reliable and may replace computed tomographic scan and diagnostic peritoneal lavage as the initial diagnostic modality in the evaluation of most patients with BAT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
96
1
4

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(105 citation statements)
references
References 22 publications
4
96
1
4
Order By: Relevance
“…In blunt trauma studies investigating FAST scanning, outcomes have demonstrated an average specificity of 90 -99% and sensitivity of 86 -99%. [4][5][6][7][8] Sensitivity in this study was therefore comparable. In accordance with previous evidence, our study also demonstrated excellent specificity of FAST (100%) regardless of mechanism of injury.…”
Section: Discussionsupporting
confidence: 55%
“…In blunt trauma studies investigating FAST scanning, outcomes have demonstrated an average specificity of 90 -99% and sensitivity of 86 -99%. [4][5][6][7][8] Sensitivity in this study was therefore comparable. In accordance with previous evidence, our study also demonstrated excellent specificity of FAST (100%) regardless of mechanism of injury.…”
Section: Discussionsupporting
confidence: 55%
“…[1][2][3] Its use has been well documented in the United States and Europe in multiple studies. Although it can clearly be an important diagnostic modality in a number of situations such as pericardial tamponade, EPs can be at a great disadvantage when performing the FAST examination since our patients are not ''prepared'' prior to the evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…ACA-DEMIC EMERGENCY MEDICINE 2002; 9:48-53 T HE focused abdominal sonography for trauma (FAST) examination is perhaps the most accepted bedside ultrasound (US) application in emergency medicine (EM) and trauma surgery. [1][2][3][4][5] While the true utility of the FAST exam is still being defined in North America, most of the issues with its use and accuracy have been settled in other countries such as Germany. 6,7 One of the difficulties encountered by emergency physicians (EPs) is trouble in adequately visualizing the required landmarks in obese and other difficult-toscan patients.…”
mentioning
confidence: 99%
“…A critical part of training is the presence of an adequate number and variability of positive examinations. The positive FAST rate is reported to be 9% to 13% [27,[40][41][42]. Thus, with 50 sequential examinations, a provider may have less than 10 positive examinations.…”
Section: Training and Credentialingmentioning
confidence: 99%